La cetra cornuta. The Horned Lyre of the Christian World - Young, Crawford (Leiden Universiteit Leiden, 2018)
My research concerns the history of a musical instrument of substantial importance in the history of Christianity, specifically in the visual arts and music culture of Romanesque, Gothic and Renaissance Italy. The cetra (also spelled cetera; in Latin, cithara) was the forerunner of the stringed instrument known in English since the 16th-c. as cittern. Because no historical artifacts or specimens have survived in instrument collections or museums, my first research task has been to establish a definitive catalog of iconographical material related to the cetra. My catalog is comprised of 54 entries, each entry referring to a monument of Italian visual art, in any medium, from c. 1100 - c. 1535. Numerousentries feature multiple depictions of this plucked instrument, bringing the total number of cetra images to well over 100 (more than half of which hitherto unpublished in organological or music history literature).The field of iconographical data presented in the catalog is then analyzed, together with relevant literary and music theory sources from the same period, to give a definitive account of the instruments morphology, evolution, construction, cultural identity and musical function. The conclusions thus arrived at are then tested and put into practice on stage: four cetre have been built for this research project by three different luthiers, and have alreadystarted to be used in concerts of early Renaissance music given in 2017.Historians and players of medieval and Renaissance instruments, may be startled by some of the essays conclusions (which disrupt current thinking on many aspects concerning the history of the cittern, including its relation to the citole), as it seeks to answer long-unanswered questions about a chordophone which time has forgotten&a stringed instrument recalling Classical Antiquity, and one of quintessential importance to both Christians and Humanists: made in Italy.
Proefschrift ter verkrijging van de graad van Doctor aan de Universiteit Leiden op gezag van de Rector Magnificus prof. mr. C.J.J.M. Stolker, volgens besluit van het College voor promoties te verdedigen op 13 juni 2018.
Keywords: Organology; Luxury; Music history